Cytotoxicity Study of Red Fruit Extract (Pandanus conoideus Lam) as Anti-Goitrogenic Herbal Medicine in Sprague Dawley Rats - Hastari wuryastuty; R. Wasito (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2014)
The use of herbal medicine (phytopharmaca) has increased manifold because of the safety. Red fruit extract is one of the supplements that has many advantages for health. The efficacy of pre-clinical trial using the rats induced by iodine deficient ration has proven that 1-2 ml of red fruit extract supplementation with/without KIO3 fortification for 30, 60 and 90 days has potency as anti-goitrogenic herbal medicine. For standarization, however, the extract red fruit has to be tested for the safety in the important organs like livers and kidneys. The research results have proven that in the normal Sprague Dawley rats, supplementation of 2 ml/day/rat of red fruit extract for 135 consecutive days has.no toxic effect in the livers and kidneys. In hyperplastic goiter Sprague Dawley rats induced by goitrogenic ration, the red fruit extract supplementation has to be in a combination with KIO3 to overcome iodine deficiency disorders and has no-toxic effect to the livers. Therefore, it can be concluded that based on pre-clinical studies using Sprague Dawley rats, the red fruit extract can be categorized as standardized anti-goitrogenic herbal medicine.